An analysis on the impact of cost control on financial performance - Mbire, Cathrine (2020)
A continuous increase in costs were cited by the management at Bak as the major causes behind the sharp reduction of annual profits between the periods 2014 to 2016.A descriptive research design was employed using a mixed approach with a targeted census population of 30 staff members most of whom were from the administrative and operations departments. A total of 30 questionnaires were distributed and 3 interviews were conducted. The research found out that poor cost control causes increase in profits, time overrun, missed targets and loss of competitive advantage thereby adversely affecting financial performance. Government policies and regulations, inflation, poor infrastructure and high labour turnover are some of the challenges faced by the organisation making it difficult to operate a well as apply cost control techniques which then negatively affects financial performance. The organisation should keep abreast with technology changes, apply tax saving strategies, outsource as well as properly manage assets so as to encounter the prior mentioned challenges so as to increase profitability, performance of workers, utilisation of resources and as well as make informed decisions thereby enhancing the financial performance of the organisation. Cost reduction should be considered as a continuous performance and not seen as a once off activity. Management should also organise a cost control committee that operates within the organisation.